On the multiplier of a group with nontrivial center - Zhmud, É. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
This paper is a sequel of [1]. On the basis of the results obtained therein, we establish inequalities that strengthen the known Green inequality for the order of the Schur multiplier of ap-group.